"Peace and Friendship": Overcoming the Cold War in the Children's World of the Pioneer Camp Artek*. Issue 3 (31st March 2022) - Neumann, Matthias
Abstract: The famous Pioneer camp 'Artek' was used by the Soviet Union to showcase socialism to upcoming generations. It was an iconic space where each summer 5, 000 children from over 60 nations met to promote transnational cooperation and Soviet-led world peace. The article reconstructs American children's experiences who dared to break through the iron curtain to participate. It will examine how, and with what success, the participants' encounters challenged and shaped their perceptions of East and West, and how their actions fed into the upsurgence of citizen diplomacy that played a crucial role in ending the Cold War.